Pengaruh Pendidikan Ekonomi Keluarga dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa - Apprillia Anggraeni Sugiarto; Fahimul Amri (Universitas Indraprasta PGRI Jakarta, 2023)
Lack of family economic education and high lifestyle pressure in the campus environment can affect student consumptive behaviour. A lack of understanding about managing finances and irrational thinking in making consumption decisions can lead to excessive spending, which leads to unhealthy consumptive behaviour. This study aims to explain the effect of family economic education on lifestyle, family economics education on consumptive behaviour, lifestyle on consumptive behaviour, and family economic education through lifestyle on consumptive behaviour of STKIP PGRI Jombang economic education students and management students at STIE PGRI Dewantara Jombang. The quantitative approach was carried out on economic education students at STKIP PGRI Jombang and management students at STIE PGRI Dewantara Jombang class of 2019–2022. Data analysis technique using path analysis. The population were 1,383 students, and the research sample were 423 students by determining proportional random sampling. The research findings revealed that there was an influence of family economic education on lifestyle, there was an influence of family economics education on consumptive behaviour, there was an influence of lifestyle on consumptive behaviour, and there was an influence of family economic education through lifestyle on consumptive behaviour.